Community Perspective in Village Fund Management in Nagur Village, Serdang Bedagai Regency - Aditia Darma Nasution, Dito; Welly, Yerisma (Basic and Applied Accounting Research Journal, 2023)
The research aims to determine the community's perspective in managing village funds in Nagur Village, Serdang Bedagai Regency. The research model was carried out using a descriptive approach with data collection techniques carried out by distributing questionnaires, observations and interviews. The research population was 100 people with a selected sample of 80 samples carried out using a purposive sampling approach. The results of the research explain that the management of village funds from a community perspective in Nagur Village produces a level of satisfaction in the "satisfied" category but has not been able to provide satisfaction at the "very satisfied" level because it has not been able to: 1) reduce the number of productive unemployment, 2) has not been able to improve the community's economy. , and 3) has not been able to provide major benefits for the economic development of Nagur Village. This is caused by the management of village funds which only focuses on physical development and ignores the development of the community's economic foundations.